The vulnerability of springs and phreatophyte communities to groundwater level declines in Oregon and Nevada, 2002–2021 - Saito, Laurel; Freed, Zach; Byer, Sarah; Schindel, Michael (Frontiers in Environmental Science, 2022)
Increased groundwater demand is causing aquifer declines that impact viability of groundwater-dependent ecosystems (GDEs) like springs and phreatophyte communities. To understand which springs and phreatophyte communities may be stressed by groundwater level declines in Oregon and Nevada, we assessed groundwater level trends in nearby monitoring wells. Very few springs and phreatophyte communities were near monitoring wells with adequate data. Less than 1% of >50,000 springs in Nevada and Oregon were within 800 m of analyzed wells, and only 52 springs were near a shallow (<30 m below ground surface) well. Among springs near analyzed wells, 56% in Nevada and 29% in Oregon were near wells with declining groundwater level trends, and percentages were similar among springs that were within 800 m of analyzed shallow wells. Less than 22% of all phreatophyte communities in Nevada and Oregon were near analyzed wells, and only 9.6% were within 800 m of a shallow well. Of phreatophyte communities near analyzed wells, 48% and 57% were near wells with declining trends in Nevada and Oregon, respectively. Differences among GDE types could reflect more groundwater development where phreatophytes exist. Differences between states in proportion of springs near wells with declining trends could be due to more surface water capture in Oregon or increased pressure for groundwater development in Nevada. State-specific policies and administration of groundwater rights and monitoring affect data availability and trends observed in the two states. More groundwater level data are essential for understanding impacts of groundwater withdrawals to GDEs.